PELATIHAN MEMBATIK KHUSUS UNTUK ANAK JALANAN DI DAERAH SEMARANG, SEBAGAI MEDIA POSITIF PENGEMBANGAN BAKAT - Avipfah, Niken Mukti; Kulsum, Umi; Widiastuti, Taning; Andira, Barta Hera; Astuti, Yuli (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Sensitizing communities against street children is lacking. Though the community of street children is a component that has the same right to get all the attention and guidance. This training aims to appreciate batik to street children as a form of devotion to the community. Batik training is done with a social approach that begins with the observation that the place has a lot of street children. Alternative non-formal education suitable to be developed on street children as batik and control emotions is one of the nations preservation of culture. Results are achieved such products handkerchief, Splash batik, batik shoes, shirts / batik shirt, batik cloth, batik brands.